Relief After COVID-19 Vaccination: A Doubtful or Evident Outcome? - Al-Hanawi, Mohammed Khaled; Alshareef, Noor; El-Sokkary, Rehab H. (Frontiers in Medicine, 2022)
Background: Since development of the first COVID-19 vaccine, the landscape of public confidence in these vaccines is uncertain. Building confidence is crucial for better preparedness of future pandemics. Following the mandatory COVID-19 vaccination policy in the country, the aim of this study was to examine whether the Saudi public feels relieved post-vaccination and to identify the factors predicting such relief. Methods: An online cross-sectional survey was conducted in July 2021 among COVID-19 vaccine recipients in Saudi Arabia. A multivariable logistic regression analysis was employed to examine and identify the variables associated with feeling relieved post-vaccination. Results: Most of the respondents (66%) stated feeling more relieved post-vaccination. Male gender [adjusted odds ratio (AOR): 1.380; 95% confidence interval (CI): 0.981-1.943] and being a student (AOR: 3.902; 95% CI: 1.674-9.096) were associated with feeling more relieved after getting vaccinated. Respondents who were concerned about becoming infected before vaccination (AOR: 0.220; 95% CI: 0.160-0.302), received two doses of the vaccine (AOR: 2.278; 95% CI: 1.630-3.182), and experienced a severe reaction after vaccination (AOR: 0.288; 95% CI: 0.165-0.504) had lower odds of feeling relieved post-vaccination. Respondents who relied on social media as the main source of vaccine-related information and those having no information about the vaccine were also less likely to feel relieved post-vaccination. Conclusions: Individuals’ attitudes toward COVID-19 vaccines may not necessarily alter post-vaccination. Although mandatory vaccination policies can significantly contribute to achieving herd immunity, public confidence toward vaccines might be eroded, which could in turn impose significant challenges in future pandemics efforts.